The real effects of credit constraints: evidence from discouraged borrowers in the euro area - Annalisa Ferrando; Klaas Mulier (European Central Bank (ECB), 2015)
This paper uses a new survey-based data set and a model with strong theoretical under-pinnings to explain the characteristics and behaviour of discouraged borrowers in the euro area. The results show that more borrowers are discouraged when the average interest rate charged by banks in a country is higher. Higher corporate tax rates, on the other hand, lead to lower discouragement. We show that discouragement has strong negative effects on in- vestment growth (-4.7pp), employment growth (-2.7pp) and asset growth (-2.9pp) due to the lack of access to bank finance in the two years following the discouragement. Furthermore, we estimate that the majority of discouraged borrowers would be unable to get a loan if they would apply. Consistent with this low loan approval likelihood, discouraged borrowers tend to be relatively risky firms.
Keywords: G01; G10; G30; G32; 330; Discouraged borrowers; real effects; static trade-off theory; survey data